Recovery of neutron-irradiated VVER-440 RPV base metal and weld exposed to isothermal annealing at 343°C up to 2,000 h - Altstadt, Eberhard; Bergner, Frank; Brandenburg, Jann-Erik; Chekhonin, Paul; Dykas, Jakub; Houska, Mario; Ulbricht, Andreas (Frontiers in Nuclear Engineering, 2024)
Neutron irradiation causes embrittlement of reactor pressure vessel (RPV) steels. Post-irradiation annealing is capable of partly or fully restoring the unembrittled condition. While annealing at high temperatures (e.g., 475°C) was successfully applied to extend the lifetime of operating VVER-440 reactors, the benefit of annealing at lower temperatures (e.g., 343°C–the maximum to which the primary cooling water can be heated) is a matter of debate. In this study, neutron-irradiated VVER-440 RPV base metal and weld were exposed to isothermal annealing at 343°C up to 2,000 h. Given the limited amount of material, the degree of recovery was estimated in terms of Vickers hardness, the ductile-brittle transition temperature derived from small punch tests, and the master curve reference temperature derived from fracture mechanics tests of mini samples. For the base metal, small-angle neutron scattering was applied to underpin the findings at the nm-scale. We have found significant partial recovery in both materials after annealing for 300 h or longer. The variations of the degree of recovery are critically discussed and put into the context of wet annealing.